PEMBERIAN INSENTIF DALAM MENINGKATKAN MOTIVASI DAN KINERJA GURU PAI SMP DI SANGATTA UTARA - Siti Norjannah; Nur Kholik Afandi (STAI Sangatta Kutai Timur, 2023)
This research aims to explore the motivation and performance of PAI teachers, the role of providing incentives in increasing the motivation and performance of PAI teachers, as well as the supporting and in hibiting factors for increasing the motivation and performance of PAI junior high school teachers in North Sangatta. The method used is a descriptive qualitative research method. The result is that more motivated teachers tend to perform better at carrying out teaching tasks. The role of providing incentives in increasing the motivation and performance of PAI teachers includes a) as a driver of PAI teacher motivation, b) improving the quality of teaching, c) providing support for performance improvement; and d) increasing the quality of Islamic teaching. Meanwhile, in supporting factors for increasing the motivation and performance of PAI teachers include support from school principals and school administration staff; PAI teachers who have access to training and professional development; awards and recognition for teacher achievements; and good relationships between PAI teachers, fellow teachers, and parents of students. Meanwhile, the inhibiting factors are excessive workload, regarding incentives and a lack of resources.